2016
DOI: 10.1111/mec.13861
|View full text |Cite
|
Sign up to set email alerts
|

MC1R variants affect the expression of melanocortin and melanogenic genes and the association between melanocortin genes and coloration

Abstract: The melanocortin-1 receptor (MC1R) gene influences coloration by altering the expression of genes acting downstream in the melanin synthesis. MC1R belongs to the melanocortin system, a genetic network coding for the ligands that regulate MC1R and other melanocortin receptors controlling different physiological and behavioural traits. The impact of MC1R variants on these regulatory melanocortin genes was never considered, even though MC1R mutations could alter the influence of these genes on coloration (e.g. by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
40
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 103 publications
4
40
1
Order By: Relevance
“…Such epistatic effects are expected from mutations at the MC1R gene given the central role of the encoded protein, which interacts with different ligands to up-or downregulate melanin synthesis (García-Borrón et al 2005). More importantly, we have recently observed an interaction between MC1R genotypes and the expression of the gene PCSK2 in determining melanin content in barn owl feathers, which is in line with a potential physiological epistatic effect of the rufous allele (San-Jose et al 2017). More importantly, we have recently observed an interaction between MC1R genotypes and the expression of the gene PCSK2 in determining melanin content in barn owl feathers, which is in line with a potential physiological epistatic effect of the rufous allele (San-Jose et al 2017).…”
Section: Differences In Color Trait Variancesupporting
confidence: 68%
See 2 more Smart Citations
“…Such epistatic effects are expected from mutations at the MC1R gene given the central role of the encoded protein, which interacts with different ligands to up-or downregulate melanin synthesis (García-Borrón et al 2005). More importantly, we have recently observed an interaction between MC1R genotypes and the expression of the gene PCSK2 in determining melanin content in barn owl feathers, which is in line with a potential physiological epistatic effect of the rufous allele (San-Jose et al 2017). More importantly, we have recently observed an interaction between MC1R genotypes and the expression of the gene PCSK2 in determining melanin content in barn owl feathers, which is in line with a potential physiological epistatic effect of the rufous allele (San-Jose et al 2017).…”
Section: Differences In Color Trait Variancesupporting
confidence: 68%
“…More importantly, we have recently observed an interaction between MC1R genotypes and the expression of the gene PCSK2 in determining melanin content in barn owl feathers, which is in line with a potential physiological epistatic effect of the rufous allele (San-Jose et al 2017). Contrarily, melanin synthesis in MC1R RW individuals (no MC1R RR individuals were available for that study) seems to be insensitive to PCSK2, despite that MC1R RW individuals show the same level of expression of this gene as MC1R WW individuals (San-Jose et al 2017). Such an effect is expected given that PCSK2 encodes a protein convertase involved in the cleavage of ACTH into α-MSH, the peptide that binds to MC1R to activate melanin synthesis (Ducrest et al 2008;Galván and Alonso-Alvarez 2009).…”
Section: Differences In Color Trait Variancesupporting
confidence: 66%
See 1 more Smart Citation
“…Since PC2 is required for generation of α-MSH, from either POMC or ACTH, this strongly suggests that α-MSH is a more important ligand than ACTH in quail, contrary to a suggestion that ACTH might be more important because of its higher binding affinity to MC1R in chicken [41]. Our results are in contrast with a study that found expression of PCSK1 , PCSK2 and POMC in chicken feather follicles [5] but similar to a study that found no detectable expression of PCSK1 in the growing feathers of barn owls ( Tyto alba ) [42]. However, the interpretation is complicated since the two breeds are apigmented (Silky chicken) and barred (Okayama-Jidori), and there was no comparison made between the patterns of gene expression between these breeds.…”
Section: Discussioncontrasting
confidence: 88%
“…To date, the majority of studies of melanin‐based traits have focused on the genes encoding the melanocortin system and characterized either genetic variation between species (Doucet, Shawkey, Rathburn, Mays, & Montgomerie, 2004; Toews et al., 2016) or how mutations in genes like the MC1R are associated with different melanin‐based phenotypes within species (Peters et al., 2016; San‐Jose et al., 2017). So far, only a single study has examined how DNA methylation may impact melanin coloration.…”
Section: Discussionmentioning
confidence: 99%